Structural integrity assessment of floating offshore wind turbine support structures - Moghaddam, Behrooz Tafazzoli; Hamedany, Ali Mahboob; Taylor, Jessica; Mehmanparast, Ali; Brennan, Feargal Peter; Davies, Catrin Mair; Nikbin, Kamran (Elsevier, 2020)
Floating offshore wind turbines are becoming more attractive to the wind industry due to their capability to operate larger turbines in deeper waters. The floating support structures are anchored to the seabed via mooring chains to impede the structure's unwanted movements. The combination of cyclic stresses and the corrosive marine environment makes the floating support structures vulnerable to corrosion pitting and subsequently fatigue crack initiation and propagation. In this study a framework is proposed to simulate fatigue crack growth from multiple corrosion pits at critical spots of the Spar-type floating support structures to examine the status of the crack during several years of operation. The proposed advanced fracture mechanics based approach provides a methodology to assess the integrity of the structure and subsequently plan for preventive or curative maintenance. The crack growth rate is examined for both singular and multiple cracks at different R ratios and for different stress levels using ABAQUS XFEM. Following numerical simulations, a sensitivity analysis is carried out using Crackwise software for different values of plate thickness, R ratio and initial crack size. The numerical results are discussed in terms of the corrosion pitting effects on fatigue life assessment of floating offshore wind turbines
Keywords: Defect assessment; Spar foundation; Floating offshore wind turbine; Corrosion fatigue crack growth; Pitting corrosion